2014
DOI: 10.15376/biores.9.3.4358-4368
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Medium Components for β-glucosidase Production in Schizophyllum commune KUC9397 and Enzymatic Hydrolysis of Lignocellulosic Biomass

Abstract: Medium components for β-glucosidase (BGL) production in Schizophyllum commune KUC9397 were optimized using a central composite design and response surface methodology. From the various medium components tested, cellulose, soy peptone, and thiamine HCl were selected as the optimal carbon, nitrogen, and vitamin sources, respectively. The highest BGL production was obtained with 2.96% cellulose, 2.30% soy peptone, and 0.11% thiamine HCl. BGL production in the optimized medium was increased 7.2-fold compared to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
(26 reference statements)
2
10
1
Order By: Relevance
“…5d showed that increasing soybean meal increased the b-glucosidase production up to a certain concentration (2.4 g) and remained almost constant thereafter. Our results are in well accordance with the work of Lee et al [29] where they used organic nitrogen source soy peptone 2.3 g giving maximum b-glucosidase activity. The predicted values were in good agreement with the values measured in these experiments, thus justifying the validity of the response model and the necessity for optimization.…”
Section: Effect Of Nitrogen Source and Its Concentrationsupporting
confidence: 93%
“…5d showed that increasing soybean meal increased the b-glucosidase production up to a certain concentration (2.4 g) and remained almost constant thereafter. Our results are in well accordance with the work of Lee et al [29] where they used organic nitrogen source soy peptone 2.3 g giving maximum b-glucosidase activity. The predicted values were in good agreement with the values measured in these experiments, thus justifying the validity of the response model and the necessity for optimization.…”
Section: Effect Of Nitrogen Source and Its Concentrationsupporting
confidence: 93%
“…Several novel families of enzymes that remove xylan side chains, such as acetyl xylan esterases [ 12 ], glucuronoyl esterases [ 13 ], and α-glucuronidases [ 14 , 15 ] have been identified in the cellulolytic system of S. commune . Among the few studies regarding its polysaccharide hydrolases, a recombinant endoxylanase from S. commune has been reported to exhibit very high level of activity against beechwood xylan [ 16 ], and crude enzymes containing mainly β-glucosidase from this fungal species could saccharify pretreated lignocellulose comparably well with a commercial β-glucosidase [ 17 ]. To date, studies of this species have focused mainly on the mating-type gene function [ 18 , 19 ] and mushroom development [ 20 , 21 ], whereas the lignocellulolytic enzymes produced by S. commune are far less characterized and a comprehensive study on its enzymatic system is still lacked.…”
Section: Introductionmentioning
confidence: 99%
“…Schizophyllum commune NAIMCC-F-03379 was able to produce comparatively high titre of cellulase enzymes as compared to previous reports (Lee et al 2014 ) with characteristics of highly thermal and pH stable, low K m (0.0909 mg/mL) and high V max (45.45 μmol/min mg) value. The partially purified enzyme showed stability at a wide range of temperature (25–65 °C) and pH (3–10) with 41% (65 °C) and 51% (pH 9) of relative activity respectively after 24 h of incubation.…”
Section: Discussionmentioning
confidence: 55%
“…The observed R 2 value was comparable with the earlier reports (Muthuvelayudham and Viruthagiri 2010 ; Wang et al 2011 ; Rajeswari et al 2014 ). The effects of media components and β-glucosidase (BGL) production have also been studied in S. commune KUC9397 by Lee et al ( 2014 ) which resulted in 7.2-fold increase in BGL activity. The requirement for fermentation for S. commune NAIMCC-F-03379 for enhanced cellulase activity is comparable to other cellulolytic microorganisms (Pachauri et al 2016 ; Premalatha et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%